Making maternity and neonatal care personalised in the COVID-19 pandemic: Results from the Babies Born Better survey in the UK and the Netherlands - Lauri M. M. van den Berg; Naseerah Akooji; Gill Thomson; Ank de Jonge; Marie-Clare Balaam; Anastasia Topalidou; Soo Downe (PLoS ONE, 2022)
Background The COVID-19 pandemic had a severe impact on women’s birth experiences. To date, there are no studies that use both quantitative and qualitative data to compare women’s birth experiences before and during the pandemic, across more than one country. Aim To examine women’s birth experiences during the COVID-19 pandemic and to compare the experiences of women who gave birth in the United Kingdom (UK) or the Netherlands (NL) either before or during the pandemic. Method This study is based on analyses of quantitative and qualitative data from the online Babies Born Better survey. Responses recorded by women giving birth in the UK and the NL between June and December 2020 have been used, encompassing women who gave birth between 2017 and 2020. Quantitative data were analysed descriptively, and chi-squared tests were performed to compare women who gave birth pre- versus during pandemic and separately by country. Qualitative data was analysed by inductive thematic analysis. Findings Respondents in both the UK and the NL who gave birth during the pandemic were as likely, or, if they had a self-reported above average standard of life, more likely to rate their labour and birth experience positively when compared to women who gave birth pre-pandemic. This was despite the fact that those labouring in the pandemic reported a lack of support and limits placed on freedom of choice. Two potential explanatory themes were identified in the qualitative data: respondents had lower expectations of care during the pandemic, and they appreciated the efforts of staff to give individualised care, despite the rules. Conclusion Our study implies that many women labouring during the COVID-19 pandemic experienced restrictions, but their experience was mitigated by staff actions. However, personalised care should not be maintained by the good will of care providers, but should be a priority in maternity care policy to benefit all service users equitably.